Redox-innocent scandium(III) as the sole catalyst in visible light photooxidations - Amal Hassan Tolba; Ahmed M. El-Zohry; Jafar Iqbal Khan; Eva Svobodová; Josef Chudoba; Jiří Klíma; Karol Lušpai; Martin Pižl; Jiří Šturala; Radek Cibulka (Nature Communications)
Abstract In recent years, the catalytic activity of scandium triflate Sc(OTf)3 has attracted significant attention due to its robust Lewis acidity and the oxophilicity of Sc3+. These features have led to impressive progress in developing diverse organic reactions, including C-C bond formation. The Sc3+ also facilitates single electron transfer in photoinduced reactions either by coordination to an organophotoredox catalyst, which modifies its redox reactivity, or by the formation of a scandium–superoxide anion complex after electron transfer from a light-absorbing redox-active compound. The prior consideration of Sc3+ as a redox-inactive/innocent metal ion initially hampered the investigation of the possibility of using Sc(OTf)3 as a sole visible light photoredox catalyst. This work demonstrates the use of Sc(OTf)3 as a visible light photocatalyst capable of direct and mild aerobic oxidative C-H functionalisation of aromatic substrates by oxidation of the benzylic position and direct cyanation of the aromatic ring.